The Dynamic of News Production in Online Media: Case Study of TvOneNews.com - Tiara Rosana Nurul Fajri; Ririt Yuniar (ULTIMA Comm, 2021)
The news content in online media is loaded with "political" interests that tend to ignore the substance and mechanism of a media. This research aims to explain that there has been a politicization of the media in the production of online news content that ignores its actual functions of the media. The study relies on qualitative research with data collection through reporting with the keyword "Bakrie" as reported by TvOneNews.com for July - August 2021 and then analyzed using qualitative content analysis methods. A phenomenon issue that needs a mapping of this textual data is related to the news that has been reported. The production process becomes the conceptual basis for the framework of this study. The media's process and function are the contents of the dynamics that occur in a media. This then raises the question of how exactly the media's production process is faced with the ideal of media functions. The results from the study showed the existence of "malasuai" between the production process and the functions of media carried out by TvOneNews.com and ideals of the Indonesian nation related to the media function as the "pillar of democracy". A suggestion for the media owners is that they should prioritize the nation's interests above personal and a suggestion for the other media crew that they should comply consistently with the journalistic code of ethics. The limitations of this research are that the data used are relatively minor, in the form of news carried out during the second wave of Covid-19 in Indonesia. This study only reviewed one media, TvOneNews.com. Keyword: production process, media function, reporting, tvonenews.com, malasuai